Stability of the Beta Phase in Ti-Mo-Cr Alloy Fabricated by Powder Metallurgy - Syarif, Junaidi (Journal of Mining and Metallurgy, Section B: Metallurgy, 2013)
A new beta Ti alloy was designed and fabricated by powder metallurgy process using pure metallic powders. The addition of Mo and Cr increased the stability of the beta phase. By contrast, O promoted alpha phase formation upon cooling. The addition of 18%Mo and 10%Cr stabilized the beta phase into ambient temperature. O increased the critical cooling rate of formation of alpha phase due to the prediction of the continuous cooling transformation diagram calculated by the Java-based Material Properties software. Sintering and solution treatment also enhanced the alloying behavior of pure powders to their designated chemical compositions. Hardness of the alloy decreased with increasing Mo and Cr content, which led to the decrease of alpha phase. The Ti-18%Mo-10%Cr alloy exhibited better corrosion resistance than a commercial Ti-6%Al-4%V alloy, which is used as current biomaterial.